An intervention of safety signs in selected primary school pupils in Perak state, Malaysia - Baharudin, Mohd Rafee; Subramaniam, Murugan; Abdul Rahman, Anita; Muhamad Saliluddin, Suhainizam (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In Malaysia, there are number of incidents highlighted by the media on school children incidents which caused injuries and death. Majority of incidents happen due to poor safety signage at the particular area where the hazards present. Current school guidelines did not specify any details on type of safety sign boards that should be in schools. So, the objective of this study is to develop, implement and evaluate the knowledge on safety signage on intervention and control group among the primary schools pupils in Perak state, Malaysia. The new design of safety signs will be intervene to reduce the unsafe act by school pupils and also to reduce the risk from unsafecondition. A cross sectional study was carried at 102 schools (91.9%) out of 111 schools in LMS district. The safety signage was designed according to MS2558:2014 standard. All the signages was added pictures and texts according to identified hazards from selected school. A self-administered questionnaires form was used to ask about the safety signage and risks. Intervention on new safety signs showed significant different between pretest, post-test 1 and post-test 2 (p<0.001). The pre-test, post-test 1 and post-test 2 result showed significant results and pupils were able to sustain the meaning of safety signage after three months’ time. The new design of safety signage able to promote safety among primary schools pupils.